AAβ public key cryptosystem - a new practical asymmetric implementation based on the square root problem - Mahad, Zahari; Kamel Ariffin, Muhammad Rezal (IEEE, 2012)
This paper aims to provide a practical implementation one of a probabilistic cipher proposed by M.R.K. Ariffin, M.A. Asbullah and N.A. Abu called as AAβ. We provide details on designing and implementing the AAβ algorithm. Furthermore, to support our understanding by providing a statistical analysis of times taken to implement the key generation, encryption and decryption algorithm for the key sizes 3072, 6144, 9216 and 12288 bits for message spaces of 4n where n = 512, 1024, 1536 and 2048 bits. We show the working of the AAβ algorithm purely from a practical standpoint to justify if it is practically implementable even for large data sets operating on large key sizes.